Peat accumulation in kettle holes: bottom up or top down? - G. Gaudig; J. Couwenberg; H. Joosten (Mires and Peat, 2006)
Rapid peat formation in kettle hole-shaped basins may take place either a) by peat forming downwards (top down) from a floating mat under stable water level conditions (terrestrialisation), or b) by peat forming upwards (bottom up) as humus colloids seal off the basin, causing the water level to rise progressively (“kettle hole mire mechanism”). The latter mechanism has hardly been considered in the international literature. The floating-mat mechanism must lead to concave peat isochrones throughout the basin, whereas the kettle hole mire mechanism will yield surface-parallel isochrones. Peat isochrones were studied in three mires occupying kettle hole-shaped basins in north-eastern Germany by comparing pollen samples from the mineral soil–peat interface at different distances from the centre of each mire with the pollen assemblage profile of a central peat core. All three mires appeared to have largely surface-parallel isochrones and must have developed by the kettle hole mire mechanism. In one mire, this mechanism alternated and took place in combination with terrestrialisation following karst subsidence. The fact that evidence of the kettle hole mire mechanism was found at all of the sites investigated indicates that it may be a common peat forming mechanism in kettle hole-shaped basins worldwide.